2014
DOI: 10.1016/j.tsf.2013.08.132
|View full text |Cite
|
Sign up to set email alerts
|

Local structure relaxation in nanocrystalline Ni1−xO thin films

Abstract: Non-stoichiometric nickel oxide (Ni 1-x O) thin films were prepared by DC magnetron sputtering technique in mixed Ar/O 2 atmosphere and studied by synchrotron radiation Ni K-edge x-ray absorption spectroscopy, x-ray diffraction and scanning electron microscopy. The use of advanced modelling technique, combining classical molecular dynamics with ab initio multiplescattering extended X-ray absorption fine structure (EXAFS) calculations, allowed us to describe the structure relaxation and dynamics in nanocrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…). In addition, it was found that, while the temperature dependence of the MSRD for the Ni-O 1 and Ni-Ni 2 atom pairs is close and can be described by the correlated Debye model, there is some additional static disorder ( st ) 2 in nanosized NiO (Anspoks et al, 2012;Anspoks, Kalinko, Kalendarev & Kuzmin, 2014) (Fig. 8).…”
Section: Figurementioning
confidence: 93%
See 3 more Smart Citations
“…). In addition, it was found that, while the temperature dependence of the MSRD for the Ni-O 1 and Ni-Ni 2 atom pairs is close and can be described by the correlated Debye model, there is some additional static disorder ( st ) 2 in nanosized NiO (Anspoks et al, 2012;Anspoks, Kalinko, Kalendarev & Kuzmin, 2014) (Fig. 8).…”
Section: Figurementioning
confidence: 93%
“…However, even in the nanosized oxide, the structural peaks are well visible up to $6 Å , thus making the use of the MD-EXAFS approach feasible. A more detailed analysis of the first two peaks due to the first two coordination shells (Ni-O 1 and Ni-Ni 2 ) indicates that, in the nanosized oxide, the R(Ni-Ni 2 ) distance increases slightly, whereas the R(Ni-O 1 ) distance contracts (Anspoks et al, 2012;Anspoks, Kalinko, Kalendarev & Kuzmin, 2014). Such a result is not trivial, since in bulk NiO the two distances are proportional:…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Application examples of this method cover several compounds: SrTiO 3 , ReO 3 (Kalinko et al, 2009), Ge (Timoshenko et al, 201), NiO (Anspoks et al, 2010;Anspoks et al, 2012;Anspoks et al, 2014a) The case of microcrystalline and nanocrystaline (6 nm) NiO (Anspoks et al, 2012) is illustrated in Fig. 5.…”
Section: Configuration-averaged Exafs Simulationsmentioning
confidence: 99%